Extrinsic experiential value as an antecedent of customer citizenship behavior - Shamim, A. (Institute of Electrical and Electronics Engineers Inc., 2015)
The research on customer citizenship behavior is getting much attention in service marketing literature. However, past researches in finding antecedents of customer citizenship behavior are limited to intrinsic value while the role of extrinsic value in customer citizenship behavior is largely ignored. The aim of this study is to fill this gap by investigating the effect of extrinsic experiential value on customer citizenship behavior. The data was collected from 800 customers of four hypermarkets located in five states of Malaysia. The covariance-based structural equation modeling approach was used to analyze the data. Findings indicate that extrinsic value has significant and positive impact on all four dimensions (feedback, helping, advocacy, tolerance) of customer citizenship behavior. The findings suggest that extrinsic value, that is, customer return on investment and service excellence, are important source for developing customer citizenship behavior. Therefore, there is dire need to focus on extrinsic value to achieve customer citizenship behavior which will subsequently lead to gain competitive advantage. Â© 2015 IEEE.